The Influence of Self Efficacy and Adversity Quotient: How is The Vocational Student Entrepreneurial Intention? - Wahyu Kurniawati; Novi Marlena (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2018)
The aims of this study is to determine the effect of self efficacy and adversity quotient on entrepreneurial intentions of students of SMK Negeri 1 Kanor Bojonegoro. This study uses descriptive research and quantitative approach. The Respondent in this study is 56 students of Grade XI of State Vocational School 1 Kanor from Marketing Department. Saturated sampling is a technique used for sampling in this study. Questionnaires and structured interviews used in data retrieval techniques. Data analysis techniques in this study used multiple linear regression equations. In this study provide conclusions: 1) there is an effect of self efficacy on entrepreneurial intentions in Grade XI SMK Negeri 1 Kanor, Department of Marketing, 2) there is an influence of adversity quotient on entrepreneurial intention in Grade XI students of State Vocational School 1 Kanor Department of Marketing, 3) there are self-influences simultaneous efficacy and adversity quotient on entrepreneurial intentions in Grade XI SMK Negeri 1 Kanor, Department of Marketing. The ability of self efficacy and adversity quotient variables explains the effect on entrepreneurial intentions by 48 percent.